Does pilocarpine-induced epilepsy in adult rats require status epilepticus? - Graciela Navarro Mora; Placido Bramanti; Francesco Osculati; Asmaa Chakir; Elena Nicolato; Pasquina Marzola; Andrea Sbarbati; Paolo Francesco Fabene (PLoS ONE, 2009)
Pilocarpine-induced seizures in rats provide a widely animal model of temporal lobe epilepsy. Some evidences reported in the literature suggest that at least 1 h of status epilepticus (SE) is required to produce subsequent chronic phase, due to the SE-related acute neuronal damage. However, recent data seems to indicate that neuro-inflammation plays a crucial role in epileptogenesis, modulating secondarily a neuronal insult. For this reason, we decided to test the following hypotheses: a) whether pilocarpine-injected rats that did not develop SE can exhibit long-term chronic spontaneous recurrent seizures (SRS) and b) whether acute neurodegeneration is mandatory to obtain chronic epilepsy. Therefore, we compared animals injected with the same dose of pilocarpine that developed or did not SE, and saline treated rats. We used telemetric acquisition of EEG as long-term monitoring system to evaluate the occurrence of seizures in non-SE pilocarpineinjected animals. Furthermore, histology and MRI analysis were applied in order to detect neuronal injury and neuropathological signs. Our observations indicate that non-SE rats exhibit SRS almost 8 (+/22) months after pilocarpine-injection, independently to the absence of initial acute neuronal injury. This is the first time reported that pilocarpine injected rats without developing SE, can experience SRS after a long latency period resembling human pathology. Thus, we strongly emphasize the important meaning of including these animals to model human epileptogenesis in pilocarpine induced epilepsy.